DAMPAK PENGGUNAAN KONTEN PADANAN ISTILAH (PI) PADA INSTAGRAM @BADANBAHASAKEMENDIKBUD TERHADAP PENYERAPAN ISTILAH FOLLOWERS-NYA (Journal of Applied Linguistics and Literature, 2024)
This research is quantitative descriptive research which aims to describe the impact of using term-equivalent content on followers' absorption of terms. The method used is a survey method with data collection techniques using questionnaires. The accumulated results state that the indicator for using content is equivalent to terms on Instagram with a percentage result of 65.62%. In the indicator of absorption of the term followers with a percentage result of 75.69%. The impact of the use of term-equivalent content on Instagram @badanbahankemendikbud on followers' absorption of terms can be seen from the various comments given by followers regarding term-equivalent content, followers' understanding of equivalent terms from foreign languages is broader, apart from that, followers' insight and vocabulary are also increase. They can understand the vocabulary that they initially misunderstood after looking at the equivalent content of the term.